Autonomous Energy Harvester Based on Textile-Based Enzymatic Biofuel Cell for On-Demand Usage - Seonho Seok; Cong Wang; Elie Lefeuvre; Jungyul Park (Sensors, 2020)
This paper presents an autonomous energy harvester based on a textile-based enzymatic biofuel cell, enabling an efficient power management and on-demand usage. The proposed biofuel cell works by an enzymatic reaction with glucose in sweat absorbed by the specially designed textile for sustainable and efficient energy harvesting. The output power of the textile-based biofuel cell has been optimized by changing electrode size and stacking electrodes and corresponding fluidic channels suitable for following power management circuit. The output power level of single electrode is estimated less than 0.5 μW and thus a two-staged power management circuit using intermediate supercapacitor has been presented. As a solution to produce a higher power level, multiple stacks of biofuel cell electrodes have been proposed and thus the textile-based biofuel cell employing serially connected 5 stacks produces a maximal power of 13 μW with an output voltage of 0.88 V when load resistance is 40 kΩ. A buck-boost converter employing a crystal oscillator directly triggered by DC output voltage of the biofuel cell makes it possible to obtain output voltage of the DC–DC converter is 6.75 V. The efficiency of the DC–DC converter is estimated as approximately 50% when the output power of the biofuel cell is tens microwatts. In addition, LT-spice modeling and simulation has been presented to estimate power consumption of each element of the proposed DC–DC converter circuit and the predicted output voltage has good agreement with measurement result.